2013
DOI: 10.1039/c3mt20260g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent silver(i) and gold(i)–N-heterocyclic carbene complexes with cytotoxic properties: mechanistic insights

Abstract: Silver(I) and gold(I)-N-heterocyclic carbene (NHC) complexes bearing a fluorescent anthracenyl ligand were examined for cytotoxicity in normal and tumor cells. The silver(I) complex exhibits greater cytotoxicity in tumor cells compared with normal cells. Notably, in cell extracts, this complex determines a more pronounced inhibition of thioredoxin reductase (TrxR), but it is ineffective towards glutathione reductase (GR). Both gold and silver complexes lead to oxidation of the thioredoxin system, the silver(I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 60 publications
9
90
0
2
Order By: Relevance
“… Structures of the ligand previously reported (left) and of the modified ligand 5 used in this work (right, see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“… Structures of the ligand previously reported (left) and of the modified ligand 5 used in this work (right, see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent papers, NHC gold(I) compounds were shown to target both TrxR isoforms preferentially in tumour cell lines rather than in normal cells [41]. TrxR inhibition determines a shift to the oxidized forms of Trx and Prx III, allowing a large increase in reactive oxygen species (ROS) [42]. The second intracellular redox system is based on GSH, kept in a reduced state by glutathione reductase (GR), which is itself reduced by NADPH.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Ag(I) and Au(I) NHC complexes bearing a fluorescent anthracenyl ligand were examined for cytotoxicity in normal and tumor cells. 28 Fluorescence microscopy experiments showed that both compounds enter cells, and are particularly efficient in penetrating tumor cells where they reach the nuclear compartment.…”
Section: Fig 1 -Structures Of Organometallic Compounds Used For Medimentioning
confidence: 99%